From dimensions, levels and domains to context-specific conceptualizations of health literacy - Atanasova Sara; Kamin Tanja (Sciendo, 2022)
Health literacy refers to skills and knowledge that enable individuals to navigate health-related information environments, to function in healthcare systems, and to practice behaviors that lead to better health outcomes. Accordingly, health literacy is one of the major preoccupations of public health scholars, policies, and strategies. However, it is a complex, multidimensional, and dynamic concept that incorporates different kinds of health-related skills and knowledge. This editorial briefly presents dimensions, levels, and domains of health literacy and discusses a growing need to acknowledge health literacy as a context-specific concept that includes various forms with context-specific conceptualizations. More specifically, it focuses on three health literacy forms that are gaining attention, namely e-health literacy, vaccine literacy, and mental health literacy. By emphasizing the importance of health literacy research for this journal and in general this editorial calls for increasing engagement in this field and invites further contributions on the topic.